MTOR suppresses autophagy-mediated production of IL25 in allergic airway inflammation. Issue 12 (18th October 2020) - Li, Wen; Wu, Yinfang; Zhao, Yun; Li, Zhouyang; Chen, Haixia; Dong, Lingling; Liu, Huiwen; Zhang, Min; Wu, Yanping; Zhou, Jiesen; Xiong, Juan; Hu, Yue; et al.
Abstract : Introduction: Airway epithelial cells are recognised as an essential controller for the initiation and perpetuation of asthmatic inflammation, yet the detailed mechanisms remain largely unknown. This study aims to investigate the roles and mechanisms of the mechanistic target of rapamycin (MTOR)–autophagy axis in airway epithelial injury in asthma. Methods: We examined the MTOR–autophagy signalling in airway epithelium from asthmatic patients or allergic mice induced by ovalbumin or house dust mites, or in human bronchial epithelial (HBE) cells. Furthermore, mice with specific MTOR knockdown in airway epithelium and autophagy-related lc3b -/- mice were used for allergic models. Results: MTOR activity was decreased, while autophagy was elevated, in airway epithelium from asthmatic patients or allergic mice, or in HBE cells treated with IL33 or IL13. These changes were associated with upstream tuberous sclerosis protein 2 signalling. Specific MTOR knockdown in mouse bronchial epithelium augmented, while LC3B deletion diminished allergen-induced airway inflammation and mucus hyperproduction. The worsened inflammation caused by MTOR deficiency was also ameliorated in lc3b -/- mice. Mechanistically, autophagy was induced later than the emergence of allergen-initiated inflammation, particularly IL33 expression. MTOR deficiency increased, while knocking out of LC3B abolished the production of IL25 and the eventual airway inflammation on allergen challenge. Blocking IL25 markedly attenuated the exacerbated airway inflammation in MTOR-deficiency mice. Conclusion: Collectively, these results demonstrate that allergen-initiated inflammation suppresses MTOR and induces autophagy in airway epithelial cells, which results in the production of certain proallergic cytokines such as IL25, further promoting the type 2 response and eventually perpetuating airway inflammation in asthma.